2021
DOI: 10.15586/aei.v49i3.73
|View full text |Cite
|
Sign up to set email alerts
|

Retinol-binding protein 4 and plasminogen activator inhibitor-1 as potential prognostic biomarkers of non-allergic asthma caused by obesity in adolescents

Abstract: Background: Non-allergic asthma caused by obesity is a complication of the low-grade chronic inflammation inherent in obesity. Consequently, the serum concentrations of adipokines such as retinol-binding protein 4 (RBP4) and plasminogen activator inhibitor-1 (PAI-1) increase. No gold standard molecule for the prediction of non-allergic asthma among obese patients has been identified.Objective: To evaluate RBP4 and PAI-1 as prognostic biomarkers of non-allergic asthma caused by obesity. Methods: A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Obesity has been shown to be associated with elevated levels of pro-inflammatory cytokines; IL-6 and highly sensitive assays for serum C-reactive protein (hs-CRP) from <2 to >7 mg/mL (Dixon et al, 2006). A study on asthma in adolescents investigated retinolbinding protein (RBP4) and plasminogen activator inhibitor (PAI-1) and found that RBP4 was useful in predicting non-allergic asthma in adolescents with obesity (Leija-Martinez et al, 2021). Therefore, RBP4 may be useful in identifying obesity-related asthma, differentiating it from other forms of asthma.…”
Section: Obesity Associated Asthmamentioning
confidence: 99%
“…Obesity has been shown to be associated with elevated levels of pro-inflammatory cytokines; IL-6 and highly sensitive assays for serum C-reactive protein (hs-CRP) from <2 to >7 mg/mL (Dixon et al, 2006). A study on asthma in adolescents investigated retinolbinding protein (RBP4) and plasminogen activator inhibitor (PAI-1) and found that RBP4 was useful in predicting non-allergic asthma in adolescents with obesity (Leija-Martinez et al, 2021). Therefore, RBP4 may be useful in identifying obesity-related asthma, differentiating it from other forms of asthma.…”
Section: Obesity Associated Asthmamentioning
confidence: 99%